(untitled) (Research, Society and Development, 2021)
The objective of this study was to observe the effectiveness of the use of proteins associated with pregnancy (PAG’s) as a method of early pregnancy diagnosis in Girolando dairy cows. By using a colorimetric reaction test, recommended for use in cows from the 28th day after service, VISUAL-PAG from "IDEXX Laboratories". The sensitivity and specificity of the test were assessed at 25, 26, 27 and 28 days post-TAI, using 57 multiparous females submitted to four sequential collections of blood samples on the days described. The material was collected by venipuncture of the coccidian vessels in vacuum tubes without anti-coagulant, processed and stored at -20ºC for later analysis. At 32 days of TAI all females were subjected to the diagnosis of pregnancy by ultrasonography (US), the Gold Test of the experiment. The results were obtained through a concordance study, which revealed 100% sensitivity and 94.7% specificity for days 25, 26, 27 and 28 post-TAI. In view of these results, it can be considered that the VISUAL-PAG kit can be used as an early and safe method of early pregnancy diagnosis in Girolando dairy cows at 25 days after artificial insemination.